Analisis Struktur Kalimat Tunggal dalam Teks Anekdot Di Situs CNN Indonesia. Com - Al Hassanah, Della; Rahmi, Iklima Hilda; Rosialasa, Nabila Ajeng Fransisca; Nur Amin, Muhamad Rizki; Lisnawati, Iis (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to examine the use of simple sentences in anecdotal texts published on CNNIndonesia.com. Employing a descriptive qualitative approach, the research analyzes five anecdotal texts titled "Baju Tahanan KPK", "Sombong", "Anak", "Kebersihan", and "Bau". Data were collected using the observe-and-note technique and analyzed through a distributional method to identify the syntactic structure of simple sentences based on the functional elements of Subject, Predicate, Object, Complement, and Adverbial (SPOK). The findings reveal that simple sentences are used effectively to deliver messages concisely and clearly. Sentence patterns such as S-P-Complement, S-P-Adverbial, and Adverbial-S-P are commonly employed to enhance the humorous, ironic, and critical tone that characterizes anecdotal texts. These findings highlight the significance of simple sentence structures in supporting effective communication in digital mediaKeywords: Kalimat Tunggal, Teks Anekdot, Struktur Sintaksis, Media Daring